Breakthrough : Mosaic - Book 5 - Grumley, Michael C. ([United States] : [Michael C. Grumley], 2019)
"The world is losing hope. Political and social infighting threaten to destroy the world. Rancor and hatred only grow stronger, engulfing entire nations. And each day moral and economic strife brings embroiled countries ever closer to war. But hope is not dead. Everywhere, pockets of human kindness and compassion continue to persevere. Where lives are cherished and virtue endures. And one small, extraordinary group fights to save us all. A team in possession of the mother of all secrets. The one secret - the one discovery - that could bring the world back from the brink."--Back cover.
"A breakthrough story."
Keywords: Evolution -- Fiction; Discoveries in science -- Fiction; Mutation (Biology) -- Fiction; Marine biologists -- Fiction; Science fiction; Thrillers (Fiction); Action and adventure fiction